Enacting Social Justice to Teach Social Justice: The Pedagogy of Bridge Builders - Eifler, Karen E.; Kerssen-Griep, Jeff; Thacker, Peter (Catholic Education: A Journal of Inquiry and Practice, 2008)
This article describes a particular endeavor, the Bridge Builders Academic Mentoring Program (BAMP), a partnership between a school of education in a Catholic university in the Northwest and a community-based rites of passage program for adolescent African American males. The partnership exemplifies tenets of Catholic social teaching, in that it is community-based, justice-oriented and in many ways countercultural. The pedagogy aligns with the goals of service learning; that is, the service extended by university students satisfies a genuine community need, and at the same time affords those engaged in service an opportunity to acquire crucial knowledge, skills, and dispositions to which they would not otherwise have access. Implications for translating this program to other contexts are provided.